Clinical Implications of Phosphorylated STAT3 Expression in De Novo Diffuse Large B-cell Lymphoma - Ok, Chi Young; Chen, Jiayu; Xu-Monette, Zijun Y.; Tzankov, Alexandar; Manyam, Ganiraju C.; Li, Ling; Visco, Carlo; Montes-Moreno, Santiago; Dybkær, Karen; Chiu, April; Orazi, Attilio; Zu, Youli; et al. (Clinical cancer research, 2014)
Purpose: Activated signal transducer and activator of transcription 3 (STAT3) regulates tumor growth, invasion, cell proliferation, angiogenesis, immune response, and survival. Data regarding expression of phosphorylated (activated) STAT3 in diffuse large B-cell lymphoma (DLBCL) and the impact of phosphorylated STAT3 (pSTAT3) on prognosis are limited. Experimental Design: We evaluated expression of pSTAT3 in de novo DLBCL using immunohistochemistry, gene expression profiling (GEP), and gene set enrichment analysis (GSEA). Results were analyzed in correlation with cell-of-origin (COO), critical lymphoma biomarkers, and genetic translocations. Results: pSTAT3 expression was observed in 16% of DLBCL and was associated with advanced stage, multiple extranodal sites of involvement, activated B-cell–like (ABC) subtype, MYC expression, and MYC/BCL2 expression. Expression of pSTAT3 predicted inferior overall survival (OS) and progression-free survival (PFS) in patients with de novo DLBCL. When DLBCL cases were stratified according to COO or MYC expression, pSTAT3 expression did not predict inferior outcome, respectively. Multivariate analysis showed that the prognostic predictability of pSTAT3 expression was due to its association with the ABC subtype, MYC expression, and adverse clinical features. GEP demonstrated upregulation of genes, which can potentiate function of STAT3. GSEA showed the JAK–STAT pathway to be enriched in pSTAT3+ DLBCL. Conclusions: The results of this study provide a rationale for the ongoing successful clinical trials targeting the JAK–STAT pathway in DLBCL. Clin Cancer Res; 20(19); 5113–23. ©2014 AACR.